PERANCANGAN VIDEO PROMOSI ARAU MINI WATERPARK PADANG - Rizky Maulana Putra, Ir. Drs. Heldi, M.Si., Ph,.D. Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of designing Arau Mini Waterpark promotional videos as promoting water attractions and games in the city of Padang. This tourist attraction was pioneered by Mr. Honanto Bastian since 2017 which is located on Jl. Batang Arau no 48 Padang. Arau mini waterpark has potential and opportunities that are big enough to be developed, so that the target audience knows the existence of Arau mini waterpark. The basic problem is the lack of optimal promotion of the Arau mini waterpark, lack of information to the target audience. The purpose of the promotional video can provide information, communicative with an attractive display of visualization to the target audience about the existence, facilities of water rides in the Arau mini waterpark.The design method uses a glass box, where the final result of a work has been drawn from a rational process. The data collection used is a 5W + 1H analysis (what, who, where, when, why and how)The results of the design as the main media video and supporting media: Posters, Billboards, Member cards, Stickers, Instagram feeds, t-shirts, towels.Keywords: Video, promotion, Waterpark.